Process Control on the Platformer with the Adaptive Neuro-Fuzzy Inference System (ANFIS) Method - Heri Setiono; Tri Yuni Hendrawati; Yustinah Yustinah (Journal of Applied Sciences and Advanced Technology, 2022)
Catalytic naphtha reform (platformer) is the main process carried out in oil refineries to increase low octane naphtha into high octane gasoline. The Reformer will meet a wide range of products that require operating flexibility. Process optimization can be done by controlling using the ANFIS method. This optimization requires an accurate process model that is applicable in a wide range of operating conditions, therefore simplifications are made in the kinetic model modeling. This model provides three temperature profiles and concentrations of important hydrocarbons (naphthene, paraffin, and aromatic) throughout the reactor. The optimal control scheme using the ANFIS method is used to maximize the aromatic yield, following the reactor inlet temperature limit. The results obtained were compared with the aromatic results without control and using control with the neural network method. The results showed that the ANFIS method has the ability to control the process. Furthermore, the results obtained from the process are used to determine the pressure of the process during the reaction.